Standard vs customized healing abutments with simultaneous bone grafting for tissue changes around immediate implants. 1‐year outcomes from a randomized clinical trial. (3rd December 2019) - Perez, Alexandre; Caiazzo, Alfonso; Valente, Nicola A.; Toti, Paolo; Alfonsi, Fortunato; Barone, Antonio
Abstract: Background: Immediate implants have shown risks of esthetic complications. The hypothesis was that a customized healing abutment could improve the peri‐implant tissue healing. Purpose: To evaluate and compare the soft and hard tissue healing around immediate implants that received bone grafting and a customized vs a standard healing abutment. Materials and Methods: Patients, who required tooth extraction and who received an immediate implant (with an alloplastic graft material) were randomly assigned to a customized or a standard healing abutment group. Clinical and radiographic examinations were taken at baseline, at 4 and 12 months. Results: Twenty‐five patients out of 61 were excluded from the study because unsuitable for immediate implantation. In total, 36 patients were randomized in the two groups. There were 17 females and 19 males (age range 23‐77). No prosthetic or implant failure was registered during the study period. The Papilla Index was significantly higher in the customized than in the standard group at 4 and 12 months ( P = .0002). The bone loss at mesial sites was significantly higher in the control than in the test group ( P = .0014). Conclusion: The customized healing abutment group showed the most favorable outcomes (in terms of PI and MBL) in case of immediate implant that received a peri‐implant bone grafting procedure.